Polyphenol, anthocyanin and resveratrol mass fractions and antioxidant properties of cranberry cultivars - Borowska, Eulalia Julitta (Array, 2009)
Summary: The study involved an evaluation of five cranberry cultivars grown in Poland: Ben Lear, Pilgrim, Stevens, Early Richard and Bergman. The reference sample comprised wild-grown common cranberry (Vaccinium oxycoccus). The mass fractions of total phenolic compounds, anthocyanins and resveratrol (HPLC-DAD), as well as the antioxidant properties (DPPH·, ·OH and ABTS+ radical scavenging capacity) were determined. Statistically significant differences (p<0.05) were reported as regards the mass fractions of polyphenols and anthocyanins in the fruit of the analysed cultivars. The highest polyphenol mass fraction was determined in Ben Lear (374.2 mg per 100 g of fresh mass), while Early Richard was the richest source of anthocyanins (77.1 mg per 100 g of fresh mass). The fruit of common cranberry contained the highest quantities of resveratrol (712.3 ng/g of fresh mass), and its mass fraction in the investigated cultivars ranged from 533.4 (cv. Stevens) to 598.2 ng/g of fresh mass (Ben Lear). Common cranberry was also marked by the highest ABTS+ scavenging capacity. Stevens and Pilgrim were characterised by a strong capability to scavenge DPPH· and ·OH free radicals. Statistically significant differences (p<0.05) were observed in respect of the free radical scavenging capacity of most investigated cranberry cultivars